PENGARUH KOMPETENSI APARATUR, PARTISIPASI MASYARAKAT, PEMANFAATAN TEKNOLOGI INFORMASI, KOMITMEN ORGANISASI, TRANSPARANSI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA (Studi pada Desa Hutatoruan IV, Desa Hutatoruan I, Hutagalung Harean Kecamatan Tarutung, Kabupaten Tapanuli Utara) - Deby Tobing; Arthur Simanjuntak; Tri Darma Sipayung; Septony Benyamin Siahaan (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2022)
The study aims to determine the effect of apparatus competence, community participation, use of information technology, organizational commitment of village government, transparency, and internal control systems on the accountability of Village Fund management in Hutatoruan IV, Hutatoruan I and Siraja Hutagalung Villages. This type of research is causal associative research with a qualitative approach. This research was conducted in Hutatoruan IV, Hutatoruan I, Siraja Hutagalung located in Tapanuli District, Tapanuli Utara Regency, North Sumatra Province. The population and samples in this study were 33 people who were 9 officials each in Hutatoruan IV, 12 people in Hutatoruan I Village, 12 Siraja Hutagalung People. This study uses primary data obtained using a questionnaire.Â While the data analysis method used in this study is the method of multiple linear regression analysis carried out with the help of SPSS 25 software. The results in this study found that the competence of the apparatus, community participation and the internal control system had a significant positive influence on the accountability of village fund management. While the use of information technology, organizational commitment, and transparency, does not have a significant effect on the accountability of village fund management.